E-accessibility Analysis in User Experience for People with Disabilities - Azizah Nurfauziah Yusril (Indonesian Journal of Disability Studies, 2020)
The purpose of writing this article is to know e-accessibility for users with disabilities. This study uses a descriptive research methodology with a qualitative approach. The subjects involved in this study were people with disabilities. Data obtained by conducting a literature study. The results of this study are the principle of e-accessibility in designing the User Interface (UI) must be considered because it will affect the User Experience (UX), so that internet users, especially users with disabilities have good accessibility so that it can be more easily to obtain information.